Accounting Remodelling pada Usaha Mikro Kecil dan Menengah (UMKM) yang Potensial Dibiayai oleh Perbankan - Dewi, Resti Kartika (Universitas Mataram, 2024)
This research aims to redesign the accounting model for micro, small and medium enterprises (MSMEs) that is suitable for banking financing. The population in this research is MSMEs in Mataram City which have the potential to be financed by banking according to the 2023 Bank Indonesia MSMEs profile database. The sample was determined using a judgment sampling method so that MSMEs with the individual business criteria